"Tantangan Kajian Kesenian Kontemporer: Ruang Publik, Pasar, dan Kekuasaan" - Tito Imanda (Antropologi Indonesia, 2012)
There are two traditions in the anthropology of art: art as abstract cultural representation and art as expression or message of the artists to their audience. This article aims to balance these two traditions as alternative approach in the study of anthropology of art. Alternative approach is needed for most studies in the anthropology of art in Indonesia encounter difficulty to explain contemporary and traditional arts in the context of contemporary society. This alternative approach offers a view that art product is a synthesis of art production and history of political economy of the society. Marshall Sahlins (1976) suggests this approach which leads us to understand that culture is a symbolic order as also popularized by Louis Althusser. Hence, this article tries to understand symbolic order in the art product by discussing relevant theories in the anthropology of art. Keywords: cultural representation, political economy, symbolic order, holistic approach